2015
DOI: 10.1140/epjc/s10052-015-3451-4
|View full text |Cite
|
Sign up to set email alerts
|

Search for dark matter, extra dimensions, and unparticles in monojet events in proton–proton collisions at $$\sqrt{s} = 8$$ s = 8 $$\,{\mathrm{TeV}}\,$$ TeV

Abstract: Results are presented from a search for particle dark matter (DM), extra dimensions, and unparticles using events containing a jet and an imbalance in transverse momentum. The data were collected by the CMS detector in proton–proton collisions at the LHC and correspond to an integrated luminosity of 19.7at a centre-of-mass energy of 8. The number of observed events is found to be consistent with the standard model prediction. Limits are placed on the DM-nucleon scattering cross section as a function of the DM … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
185
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 326 publications
(190 citation statements)
references
References 83 publications
5
185
0
Order By: Relevance
“…Gravitational evidence for dark matter (DM) is well established [1][2][3], yet DM still evades all other means of detection [4][5][6][7][8]. A current focus of the search for DM is indirect detection: DM annihilation or decay could produce observable Standard Model (SM) particles, including photons.…”
Section: Introductionmentioning
confidence: 99%
“…Gravitational evidence for dark matter (DM) is well established [1][2][3], yet DM still evades all other means of detection [4][5][6][7][8]. A current focus of the search for DM is indirect detection: DM annihilation or decay could produce observable Standard Model (SM) particles, including photons.…”
Section: Introductionmentioning
confidence: 99%
“…We have found that the most stringent bounds on parameters of the model in question are obtained for the cut E miss T > 500 GeV. Note that E miss T in [21] is defined as the magnitude of vector sum of transverse momentum of all particles in the event. For our calculations this means that E miss T coincides with transverse momentum of jet, p j T .…”
Section: Lhc Boundsmentioning
confidence: 98%
“…Here we discuss bounds on the model parameters from results of LHC searches for monojet and missing energy signature [19][20][21]. Sensitivity of the collider (Tevatron and LHC) searches to hylogenesis model has been discussed in [13].…”
Section: Lhc Boundsmentioning
confidence: 99%
See 2 more Smart Citations